2016
DOI: 10.9775/kvfd.2016.15036
|View full text |Cite
|
Sign up to set email alerts
|

Köpeklerde Patellar Luksasyonda Kıkırdak Erozyonunun Prevalansı ve Etkilenmiş Eklemlerdeki Gen Ekspresyonu

Abstract: The objectives of this study were to assess the prevalence of cartilage erosion in small dogs with patellar luxation (PL), and related osteoarthritis (OA)-related gene expression. In Study 1, 71 dogs were examined to determine risk factors associated with PL, including breed, age, weight, sex, and affected joint. In Study 2, a total of 39 dogs were divided into four groups: normal articular cartilage in the stifle joint (G1; n=5); PL without cartilage erosion (G2; n=11); PL with cartilage erosion (G3; n=14); a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…There were no pathological findings on the lateral ridge of femoral condyle. In agreement with the previous studies, the most area of eroded cartilage on femoral condyle were found on the medial trochlear ridge performing by gross examination (Alam et al, 2011;Boonsri et al, 2016;Jahrupatrakorn, 2017). Cartilage lesions are subsequently appeared due to the luxation of patella (Daems et al, 2009;Vollnberg et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…There were no pathological findings on the lateral ridge of femoral condyle. In agreement with the previous studies, the most area of eroded cartilage on femoral condyle were found on the medial trochlear ridge performing by gross examination (Alam et al, 2011;Boonsri et al, 2016;Jahrupatrakorn, 2017). Cartilage lesions are subsequently appeared due to the luxation of patella (Daems et al, 2009;Vollnberg et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…In the non-recurrence group, the dates were record from the surgery date to the end of December, 2015. The recurrence rate was compared between the grade of patellar luxation (1)(2)(3)(4), and between the unilateral and the bilateral patellar luxation.…”
Section: Recurrence Ratementioning
confidence: 99%
“…As well documented, in small animal orthopedics, patellar luxation is one of the most common joint diseases in dogs, particularly small breed dogs [1][2][3][4] . Consequence of this disease being left untreated is that it can cause many complications and disorders such as cranial cruciate rupture [1,5] , cartilage erosion [2,6] , and osteoarthritis [7,8] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation